KUALITAS PELAYANAN DAN SEMANGAT KERJA PENGARUHNYA TERHADAP KEPUASAN PENGGUNA LAYANAN PADA KANTOR BERSAMA SAMSAT TANDES SURABAYA - jurnalmap map; Valensius Jemada; Sri Juni Woro Astuti; Arini Sulistyowati (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2019)
ABSTRACT This study aims to describe the quality of service and the morale of its influence on service user satisfaction in the Joint Office of Samsat Tandes Surabaya. Furthermore, to find out the relationship both partially and simultaneously service quality and morale towards service user satisfaction in the Joint Office of Samsat Tandes Surabaya. This type of research is explanatory research. The sample in this study was 83 employees in the Joint Office of Samsat Tandes Surabaya. The results showed that the variable quality of service and spirit of work together (simultaneous) had a significant effect on customer satisfaction in the Joint Office of Samsat Tandes Surabaya. Variable variables of service quality and significant partial spirit of work towards customer satisfaction in the Joint Office of Samsat Tandes Surabaya. Keywords: customer satisfaction, service quality, spirit of work